Étude Évaluative D’examen Normalisé De Sciences De La Vie Et De La Terre Au Cycle Secondaire Collegial - Abdellah El Allaoui; Fouzia Rhazi Filali; El mokhtar El Hadri; Khalid Fetteh; Malika Bouhadi (European Scientific Journal, ESJ, 2016)
Generally an exam, a performance test or a test to be used for summative or evaluation purposes must be prepared according to a definite plan. The present paper aimed at analyzing and evaluating the certificate exam, the study also revealed the questions representation of Bloom's cognitive levels. This article presents also the statistical and psychometric indices that characterize each of the questions (26 items) that make up a certification exam of the Sciences of Life and Earth in a Moroccan high school in Meknes. Indeed, two hundred test copies have been analyzed using the SPSS and Anitem software. The average of goals achieved in activities of knowledge, analysis, understanding and evaluation is 61%, 52%, 37.5%, 58% respectively, but it is only 19% for "application" activity. The success rate in open questions items is only 38.5% against 61.5% for Multiple Choice Questions (MSQ) and closed questions. The internal homogeneity coefficient is greater than 0.8 (α = 0.84), which means that the homogeneity of the instrument has been considered satisfactory. According to the index of difficulty out of the 26 items, two are extremely inferior (P> 0.8), while two others are extremely superior (P <0.2). According to the index of discrimination eleven items meet the conditions of validity, three are not discriminating and twelve should be reviewed. The correlation between the success rate in these items and their difficulty index is high (R = 0.98). In light of the findings, we recommended the necessity of having measurement and evaluation experts in writing questions of exams and we highly recommend the necessity of continuous training of teachers in the field of assessment and evaluation.